Electrochemical synthesis of silver nanoparticles in solutions of rhamnolipid. (1st October 2020) - Kuntyi, Orest; Mazur, Artur; Kytsya, Andriy; Karpenko, Olena; Bazylyak, Liliya; Mertsalo, Ivanna; Pokynbroda, Tetiana; Prokopalo, Alla
Abstract : The electrochemical method of synthesis of silver nanoparticles (AgNPs) using 'sacrificial' silver anode as a source of Ag +, microbial origin surfactant (rhamnolipid, RL) as a stabiliser of AgNPs and electric current as a reducer is presented. Using of cyclic voltammetry it was determined that RL concentration and temperature are the main factors influencing the rate of anodic dissolution of silver and cathodic reduction of the formed complex [AgRL] + . Increasing of RL concentration leads to increasing of the cathodic currents that indicate the increase of the rate of AgNPs formation. With increasing the temperature from 40 to 60°C the values of the anode and cathodic currents increase to 1.5 times, this indicates the predominant diffusion nature of the influence of the temperature on the synthesis of AgNPs. Obtained AgNPs were investigated using transmission electron microscopy and it was found that increasing of concentration of surfactant leads to decreasing of the size of AgNPs, whereas increasing of temperature, on the contrary, leads to increasing of mean size of AgNPs. Synthesised AgNPs showed significant antimicrobial activity against the bacterial phytopathogens Xanthomonas campestris and Agrobacterium tumefaciens . It has been shown that AgNPs stabilised by RL are characterised by low phytotoxicity.